Analysis and implementation of artificial immune system on embedded system to solve optimization problems - Khamish Varan a/l Balachandran (2023)
Artificial Immune System (AIS) are adaptive systems, inspired by theoretical immunology and observed immune functions, principles and models, which are applied to problem solving.